"You are activated, proud of it": A Study of Learner Identified Impacts of Participation in Adult Literacy Programs - Mary Beth Bingman; Olga Ebert (Adult Education Research Conference, 1999)
This study is based on life history interviews with ten adult literacy students. It examines how adults describe the impacts of their participation in adult literacy classes on their lives, and how the impacts they define compare with performance measures in the new Workforce Investment Act.